Analisis Strategi Manajemen Piutang dalam Mengurangi Potensi Risiko Piutang Tak Tertagih pada PT ABC - Dwita Diajeng Syawaliah; Oryza Tannar (Jurnal IAKP : Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2025)
Credit sales are a common strategy employed by companies to boost sales volume and expand market reach. However, this strategy also carries the risk of uncollectible receivables, which can negatively affect the company’s financial liquidity. This study aims to analyze the receivables management strategies implemented by PT ABC in mitigating the potential risk of uncollectible receivables. A qualitative descriptive approach was used, with data collected through observation, literature review, and direct interviews with relevant parties. The findings reveal that the company applies a series of strategies, including customer creditworthiness evaluation, the use of guarantees such as SKBDNs and checks, flexible installment payment options, and a phased collection procedure involving reminders, visits, and legal notices. These strategies have proven effective, as indicated by the declining trend in uncollectible receivables over the past three years, from 2022 to 2024. The study concludes that effective receivables management, supported by an integrated accounting system and consistent procedures, can minimize the risk of losses and maintain the company’s financial stability